Hemoderivados rico em plaquetas na oftalmologia veterinária de pequenos animais: revisão da literatura - Rodrigues, Gabriele Porfírio (Universidade Estadual Paulista (Unesp), 2022)
Regenerative medicine and the use of blood products is an expanding area considering the favorable results of its application in various tissues. Platelet-rich plasma (PRP) is a blood component obtained from the whole blood centrifugation, producing a biomaterial with platelets and concentrated growth factors. Fibrin-rich plasma (PRF), on the other hand, belongs to a more recent generation of platelet concentrates, with simplified preparation and without biochemical manipulation of the blood, being transformed into biological gel or glue. The specific biomaterial for the ocular surface, called E-PRP, comes in three main products: injectable form, capable of accelerating corneal healing; topical, which is easy to prepare and store, as well as the absence of preservatives; and solid plug, an option for cases with extensive stromal loss. Meanwhile the PRF, mainly in the form of glue, promotes sealing, healing and epithelialization of the cornea. Therefore, there is an indication and therapeutic potential for the use of blood products, especially E-PRP and PRF, in various ocular deseases, especially ulcer and keratoconjunctivitis sicca, since they stimulate chemotaxis and cell proliferation and present antimicrobial and immunological modulation activity. Although researches demonstrate significant clinical-surgical advantages, further studies in animals should be encouraged, considering the diversity of weight and lower blood volume available, in order to contribute to its therapeutic use in veterinary ophthalmology

A medicina regenerativa e o uso de hemoderivados é uma área em expansão considerando os resultados favoráveis de sua aplicação em diversos tecidos. O Plasma rico em plaquetas (PRP) é um componente sanguíneo obtido a partir da centrifugação do sangue total, produzindo um biomaterial com plaquetas e fatores de crescimento concentrados. Já o Plasma rico em fibrina (PRF) pertence a uma geração mais recente de concentrados de plaquetas, com preparação simplificada e sem manipulação bioquímica do sangue, sendo transformado em gel ou cola biológica. O biomateral específico para a superfície ocular, denominado E-PRP, apresenta-se em três produtos principais: forma injetável, capaz de acelerar cicatrização da córnea; tópica, que apresenta facilidade de preparação e armazenamento, bem como ausência de conservantes; e tampão sólido, opção para casos com extensa perda estromal. Já o PRF, principalmente na forma de cola, promove vedação, cicatrização e epitelização da córnea. Portanto, há indicação e potencial terapêutico no uso de hemoderivados, em especial o E- PRP e PRF, nas diversas doenças oculares, principalmente úlcera e ceratoconjuntivite seca, uma vez que estimulam quimiotaxia e proliferação celular e apresentam atividade antimicrobiana e de modulação imunológica. Embora pesquisas demonstrem significativas vantagens clínico-cirúrgicas, maiores estudos devem ser incentivados em animais, considerando a diversidade de peso e menor volume sanguíneo disponível, a fim de contribuir para o uso terapêutico na oftalmologia veterinária.
Platelet-rich blood derivatives in small animal veterinary ophthalmology: literature review
Keywords: Ophthalmology; Animals; PRP; PRF; Animais; Oftalmologia